Analysis of Seismic Damage Modes of Landslides Containing Tunnels under Horizontal Earthquake Action. (14th November 2022) - Sun, Hao; Wu, Honggang; Ma, Zhigang; Yuan, Zhou; Feng, Kang
Abstract : With the vigorous development of railway and highway construction, tunnel construction often follows the mountains and rivers, crossing high-intensity landslide areas, and potential earthquakes triggering damage in areas including tunnel landslides have become a hot issue today. Based on this, this paper performs a shaker test on the tunnel-containing landslide body, inputs horizontal seismic waves, and tests the acceleration response data of different bits in the landslide body. By analyzing the temporal and frequency domain transformations of the acceleration response at different positions in the slope body combined with the deformation characteristics of the slope, and then analyzing the seismic response of the slope under the action of the front and back seismic sequences, the results show that (1) the existence of the tunnel has the effect of energy dissipation and vibration reduction, making the energy input at T8, and the measuring point on the upper part of the tunnel at the lowest. (2) When the seismic wave is transmitted, it will cause reflection around the tunnel, forming complex seismic wave field, resulting in the irregular distribution of acceleration amplification coefficient. (3) There is a high correlation between seismic responses of different levels. When the acceleration response of the preseismic response to the landslide-containing tunnel is not considered, the acceleration response of the postseismic response to the slope and the structure will be lower than the real value. (4) The sequence of failure at different locations of landslide mass containing tunnel is found through marginal spectrum analysis. It is concluded that the failure mode of landslide mass with tunnel is extrusion and sliding out of the middle slope. The research results can provide some reference for the reinforcement design of landslide with tunnel in high-intensity area.